Application Scope and Limitations of TADDOL-Derived Chiral Ammonium Salt Phase-Transfer Catalysts - Gururaja, Guddeangadi N. (MDPI, 2013)
We have recently introduced a new class of chiral ammonium salt catalysts derived from easily available TADDOLs. To get a full picture of the scope of application and limitations of our catalysts we tested them in a variety of different important transformations. We found that, although these compounds have recently shown their good potential in the asymmetric α-alkylation of glycine Schiff bases, they clearly failed when we attempted to control more reactive nucleophiles like β-keto esters. On the other hand, when using them to catalyse the addition of glycine Schiff bases to different Michael acceptors it was found necessary to carefully optimize the reaction conditions for every single substrate class, as seemingly small structural changes sometimes required the use of totally different reaction conditions. Under carefully optimized conditions enantiomeric ratios up to 91:9 could be achieved in the addition of glycine Schiff bases to acrylates, whereas acrylamides and methyl vinyl ketone gave slightly lower selectivities (up to e.r. 77:23 in these cases). Thus, together with additional studies towards the syntheses of these catalysts we have now a very detailed understanding about the scope and limitations of the synthesis sequence to access our PTCs and about the application scope of these catalysts in asymmetric transformations.